2008
DOI: 10.1158/0008-5472.can-08-2582
|View full text |Cite
|
Sign up to set email alerts
|

A Mutant Collagen XIII Alters Intestinal Expression of Immune Response Genes and Predisposes Transgenic Mice to Develop B-Cell Lymphomas

Abstract: Epithelial cells of mucosal surfaces are critical for maintaining immune homeostasis by aiding in the discrimination of pathogenic and commensal microorganisms and modulating the activities of antigen-presenting cells and lymphocytes. Functional breakdowns resulting in chronic infection and inflammation are associated with the development of hematologic and solid neoplasms for which detailed pathogenetic mechanisms are poorly understood. Mice heterozygous for a transgene Col13a1 del expressing a mutant collage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…LTBP3 secretion is known to be dependent upon co-expression of TGF-beta24 which is a key pro-fibrogenic cytokine that is activated in chronic inflammation and leads to collagen deposition 25,26. COL13A1 has been previously linked with modifying inflammatory response genes in intestine 27. A recent GWAS study showed that EFCAB4B is associated with hypertension in Chinese population 28.…”
Section: Discussionmentioning
confidence: 99%
“…LTBP3 secretion is known to be dependent upon co-expression of TGF-beta24 which is a key pro-fibrogenic cytokine that is activated in chronic inflammation and leads to collagen deposition 25,26. COL13A1 has been previously linked with modifying inflammatory response genes in intestine 27. A recent GWAS study showed that EFCAB4B is associated with hypertension in Chinese population 28.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular functions have also been implicated in a mouse model for Alport syndrome, where collagen XIII expression was found to be induced in the inflamed kidney endothelium, mediating selective recruitment of ␣1␤1 integrin-positive monocytes to the kidney (Dennis et al, 2010). Furthermore, collagen XIII affects the immune system, as shown with mice expressing a low dose of the truncated dominant-negative minigene mentioned above, which develop B-cell lymphomas and present heightened expression of immune response genes in the gastrointestinal tract (Tuomisto et al, 2008). Interestingly, COL13A1 was classified as a prognostically favourable molecule in large-B-cell lymphomas (Lenz et al, 2008).…”
Section: Biological Functionsmentioning
confidence: 97%
“…Being derived mostly from mesenchymal cells, collagen XIII is found in practically all tissues studied, often in association with BMs, e.g. in blood vessels or junctional structures such as myotendinous and neuromuscular junctions (MTJ and NMJ) and the periosteum Sund et al, 2001a;Tuomisto et al, 2008;Kvist et al, 2001;Latvanlehto et al, 2010;Ylönen et al, 2005). The highest local concentrations of collagen XIII identified in a ␤-galactosidase reporter mouse model generated by homologous recombination were in the postnatal NMJ and the periosteum (Latvanlehto et al, 2010).…”
Section: Expression Activation and Turnovermentioning
confidence: 99%
See 1 more Smart Citation
“…For example, COL13A1 is the most highly down-regulated in thyrospheres, which express 521-fold lower levels than do monolayer cells (p=0.0000207). It encodes the alpha chain of one of the nonfibrillar collagens [20]. The function of this gene product in ATC is unknown.…”
Section: Resultsmentioning
confidence: 99%